The Effect of Gyro tonic Exercises on Developing Specific Strength and Performance Achievement in Young Rowers (2000 Meters) - Daher, Ayad (Journal of Physical Education, 2025)
This study aimed to investigate the effect of Gyro tonic exercises on developing specific strength (speed-strength and strength endurance) and performance achievement in young rowers over a 2000-meter distance. An experimental approach was adopted, applying an 8-week training program to a sample of 8 rowers from the training center in Al-Karkh. The program included Gyro tonic exercises and core stability training to enhance the players' physical and skill performance. The results revealed statistically significant differences between pre- and post-tests in all studied variables, indicating that Gyro tonic training significantly improved muscular strength and performance achievement. The researcher attributes this improvement to the controlled application of training in terms of intensity, volume, and rest periods, which enhanced physical and skill performance. The findings align with previous studies indicating that Gyro tonic exercises improve flexibility, strength, and muscular coordination while enhancing mental and physiological aspects. The results emphasize the importance of incorporating such exercises into rowers' training programs to optimize athletic performance. The researcher recommends using Gyro tonic training to improve rowers' physical and technical performance and conducting further studies on Gyro tonic exercises with different programs and equipment to generalize benefits across other sports.